Polysemy and Semantic Extension of Lexeme Hot - Pasaribu, Truly Almendo (LLT Journal: A Journal on Language and Language Teaching, 2014)
Polysemy is a well-known fact about language. This study focuses on describing the concept and the extended senses of lexeme hot found in the corpus. The data taken from the corpus show that lexeme hot contains more than one semantic representation. This study aims at finding out the prototypical meaning, the extended senses and the relation between the prototypical meaning and the extended senses. First, the paper discusses the literal meaning of hot from its componential analysis, which will be supported by the Natural Semantic Metalanguage. After elaborating the prototypical meaning of the lexeme hot, this paper elaborates the extended senses of the lexeme and the motivation grounding the various types of these senses. Finally, it analyses the relation of the literal and the extended senses of the word by drawing the semantic networks. This research elaborates 10 extended senses of the word hot found in the corpus. The prototypical meaning of the word indicates a very high degree of temperature. It is a scale used to describe high degree of temperature. The senses of lexeme hot are mostly motivated by metaphoric extension, in which hot is used to describe a scale to measure other things. The relation of the senses enables us to draw the semantic network of the polysemy of lexeme hot.